Courage and Conviction : An Autobiography - Singh, V. K., 1944- and Verma, Kunal (New Delhi Aleph Book Company, 2013)
Autobiography of a retired General of Indian Army
Include Illustration and Index
Keywords: India -- Armed Forces--Officers -- Generals